Cytogenetic bioassays as tools to distinguish between toxic and non-toxic varieties of Jatropha curcas (Euphorbiaceae) - Fonseca Andrade-Vieira, Larissa (2018)
The tropical and subtropical naturalized physic nut (Jatropha curcas L.), has been explored for biodiesel production in recent times. The oil is extracted from the seeds and, for the production to be feasible, utilization of the residual seed cake is crucial. Although the cake could be employed as a protein source in animal feed, it is rich in phorbol ester, which is toxic for animals. Therefore, breeding programs have been working to reduce or eliminate the phorbol ester content in physic nut. In this context, the present work aimed to evaluate the physic nut oil of toxic and non-toxic varieties (containing known or undetectable amounts of phorbol ester, respectively) with regards to phytotoxicity in a model experiment with Lactuca sativa L. For this, the percentage of germinated seeds was evaluated after 8, 16, 24, 36 and 48 hours of exposure to the treatments with toxic and non-toxic oil at concentrations of 22.5 %, 45 % and 67.5 % of emulsion (physic nut oil energetically mixed with distilled water). Root growth was determined after 48 hours of exposure and the germination speed index was obtained. The different stages of mitotic division as well as possible chromosomal and nuclear alterations were also recorded. The mitotic index was calculated as the number of dividing cells, as a fraction of the total number of cells, and the frequency of chromosome and nuclear alterations, expressed as the percentage of number of alterations divided by the total number of cells. Both varieties exhibited phytotoxicity, inducing significant reductions in percentage of germinated seeds (reduction of 98 %), germination speed index (reduction of 24.44) and root growth (reduction of 8.54 mm). In microscopic analysis, a mitodepressive effect was observed for both oils at the three concentrations used when compared to the negative control; however, it was possible to distinguish between the toxic and the non-toxic varieties based on the more expressive reduction of division promoted by the first, 2.19 %. Significant increments in the frequency of mitotic cells showing chromosome alterations as well, as the presence of condensed nuclei, were observed in the treated cells. However, these parameters were not significantly different from the control in the cells treated with both physic nut oils. In conclusion, the evaluation of root growth and cell division in the plant model L. sativa, can be proposed as an alternative to animal tests to distinguish the varieties with high and low phorbol ester concentration, thus contributing to the detection of toxicity in varieties used in breeding programs. Rev. Biol. Trop. 66(2): 495-502. Epub 2018 June 01.